In Vitro and In Silico Cytotoxic and Antibacterial Activities of a Diterpene from Cousinia alata Schrenk - Almira Zhanzhaxina; Yerlan Suleimen; Ahmed M. Metwaly; Ibrahim H. Eissa; Eslam B. Elkaeed; Raigul Suleimen; Margarita Ishmuratova; Kydyrmolla Akatan; Walter Luyten (Journal of Chemistry)
A biologically guided isolation of secondary metabolites from Cousinia alata Schrenk wild plant growing in Akmola region, Kazakhstan, led to the isolation of the bioactive diterpene grindelic acid (1). Six flavonoids were also isolated and identified as retusine (2), pachipodol (3), jaranol (4), penduletin (5), casticin (6), and 5, 7, 3′-trihydroxy-3, 4′-dimethoxyflavone (7). Penduletin (5) showed moderate cytotoxic activity assay. Grindelic acid exhibited promising cytotoxic activity against the Artemia salina nauplii and antibacterial activity against Staphylococcus aureus, Bacillus cereus, and Salmonella enteritidis. The presence of the essential pharmacophoric features of histone deacetylase (HDAC) inhibitors in the structure of grindelic acid encouraged us to run a molecular docking study against the HDAC enzyme to understand its mechanism of action on a molecular level. Grindelic acid showed a binding mode of interaction similar to that of the cocrystallized ligand and exhibited good binding affinity against HDAC with the binding free energy of −18.70 kcal/mol. The structures of isolated compounds were determined by MS, 1D, and 2D NMR spectroscopy methods. Compounds (1–7) were isolated for the first time from Cousinia genus.